2011
DOI: 10.1111/j.1365-2664.2011.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse marsh plant communities are more consistently productive across a range of different environmental conditions through functional complementarity

Abstract: Summary 1.Understanding the influence of biodiversity on ecosystem functionality is crucial in modern ecosystem management, especially with regard to the resistance and resilience of ecosystems to future environmental changes. In this study, we assessed the effects of three different environmental regimes on the relationship between diversity and biomass production among marsh plants in comparison with a control treatment to elucidate the underlying classes of proximate mechanisms. 2. We subjected assemblages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Confirming other studies7913141516, we found that envionmental stress changed the biodiversity–ecosystem function relationship (Fig. 1, Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Confirming other studies7913141516, we found that envionmental stress changed the biodiversity–ecosystem function relationship (Fig. 1, Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…In general, complementarity is fundamental in explaining stability and resilience in highly diverse systems ( Fig. 3; Cardinale et al, 2007;Steudel et al, 2011). However, increased trait diversity cannot be assumed to always be associated with community stability (Loreau & Behera, 1999).…”
Section: Mechanisms For Plant Community Resiliencementioning
confidence: 99%
“…In aquatic systems positive biodiversity effects were observed in manipulation experiments, i.e., experiments in which biodiversity was artificially manipulated to simulate species loss or artificial communities, with higher plants [20,32,33], macroalgae [34][35][36][37][38], and microalgae [22,[39][40][41][42]. Manipulation experiments with species from oceanic systems show a positive biodiversity-ecosystem functioning effect for primary producers, i.e., plants and algae [33].…”
Section: General Questions Applied On Microalgae Models Ecosystem Funmentioning
confidence: 99%
“…Ecosystems can be stressed to some degree without direct destruction of the functioning of the system, but a decrease of functioning was found in several systems [19][20][21][22].…”
mentioning
confidence: 99%